Three new species of the genus Aemene Walker (Lepidoptera: Erebidae: Arctiinae) from the Himalayas - Volynkin, Anton V. (Zootaxa, 2021)
Three new species of the genus Aemene Walker, 1854 are described: Aemene cernyi sp. n. (NE India and E Nepal), Aemene laszloi sp. n. (C Nepal) and Aemene bucseki sp. n. (C Nepal and Pakistan). The Aemene taprobanis Walker, 1854 species-group is established and characterised. The status of one taxon previously considered as a junior synonym of A. taprobanis is revised: Aemene sinuata Moore, 1878, stat. rev. A taxon previously considered as a subspecies of A. taprobanis is upgraded to species level: Aemene likiangensis (Daniel, 1951), stat. nov. Lectotypes are designated for Aemene taprobanis Walker, 1854, Panassa cingalesa Walker, 1865, Autoceras grammophora Felder, 1874 and Aemene sinuata Moore, 1878. Adults together with the male and the female genitalia of the new and related species are illustrated.